A catalyst carrier and its preparation method and application

By forming a nitrogen-doped carbon coating layer on the surface of the carbon nanotube support and dispersing CeO2, the problem of insufficient agglomeration and active sites of the carbon nanotube support is solved, the dispersion of the catalyst and the proton conduction ability are improved, and the fuel cell membrane is extended The service life and improve catalytic activity.

CN115739156BActive Publication Date: 2024-12-20CHINA AUTOMOTIVE INNOVATION CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202211486416.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2024-12-20
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

As catalyst support, existing carbon nanotubes have problems such as agglomeration, few active sites and difficult to control, which affect catalytic activity and performance.

Method used

Using nitrogen-doped carbon coating and cerium oxide (CeO2) as catalyst support, the nitrogen-doped carbon coating is formed on the surface of the carbon support and dispersed CeO2 evenly, thereby reducing the van der Waals force between the carbon support and improving dispersion. Sexual and active sites.

Benefits of technology

It improves the dispersion and proton conduction ability of the catalyst support, extends the service life of the proton exchange membrane, and improves the catalytic reduction activity and electrochemical activity area of ​​the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115739156B_ABST
    Figure CN115739156B_ABST
Patent Text Reader

Abstract

The present invention discloses a catalyst carrier and a preparation method and application thereof, wherein the catalyst carrier comprises a carbon carrier, a nitrogen-doped carbon coating layer and CeO2, wherein the nitrogen-doped carbon coating layer is coated on the surface of the carbon carrier, and the CeO2 is dispersed in the nitrogen-doped carbon coating layer, wherein the carbon carrier is a carbon nanotube and / or fullerene. The nitrogen-doped carbon coating layer provides more active sites for CeO2, so that CeO2 is uniformly dispersed in the nitrogen-doped carbon coating layer, and in addition, the nitrogen-doped carbon coating layer and CeO2 weaken the van der Waals force between the carbon carriers, effectively improving the dispersibility of the carbon carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts and relates to a catalyst carrier and a preparation method and application thereof. Background Art

[0002] As a new generation of new energy, hydrogen fuel cells are an efficient, environmentally friendly and sustainable energy source with the advantage of zero pollution. In proton exchange membrane fuel cells, hydrogen is introduced into the anode and oxygen or air is introduced into the cathode. The catalyst of the electrode promotes the redox reaction of the anode and cathode fuels, and generates water (2H2+O2=2H2O) through chemical reaction. The core component of the proton exchange membrane fuel cell, the membrane electrode, mainly includes five layers. The middle layer is the proton exchange membrane, which has the function of blocking gas and transmitting protons. Taking the catalyst / proton exchange membrane assembly (CCM) as an example, a catalyst with catalytic function is coated on both sides of the proton exchange membrane, and its main function is to reduce the activation energy of hydrogen and oxygen reaction. The outermost layer is a porous and conductive gas diffusion layer, including a microporous layer and carbon paper, which mainly functions to transmit electrons, drain gas and water, and support. Among them, the catalysts for fuel oxidation and oxygen reduction are usually based on Pt / C and PtCo / C, and the platinum or platinum alloy catalyst uses a carbon carrier as the carrier medium. There are many types of optional carbon carriers, mainly including carbon powder, carbon nanotubes, carbon nanowires or graphene.

[0003] Using carbon carrier as catalyst carrier medium is a direction of current catalyst carrier research and development. There are many shortcomings in using carbon nanotubes directly as carrier medium, such as carbon nanotubes are prone to agglomeration, less functionalized sites and relatively small specific surface area. For example, CN107649148A discloses a method for preparing platinum / nickel catalysts using multi-walled carbon nanotubes as carriers. The patent first treats the surface of multi-walled carbon nanotubes with nitric acid and sulfuric acid to make their surfaces have certain active functional groups, then adds metal platinum and nickel precursors, ultrasonically disperses and dry roasts, and finally reduces to obtain PtNi / MWCNT catalysts. For example, CN114990579A discloses a platinum-boron co-doped supported palladium-based catalyst and its preparation method and application. The patent is to fully mix the precursors of platinum and palladium with the carbon carrier in a solution, use dimethylamino borane as a boron source and reduce, and then carry out high temperature annealing treatment on the resulting product, thereby obtaining a platinum-boron co-doped supported palladium-based catalyst. For example, CN115000424A discloses a Pd hydride catalyst for direct alcohol fuel cells and a preparation method thereof, wherein a Pd precursor salt is dissolved in deionized water to prepare a Pd salt solution, a carbon carrier is dispersed in a reaction solvent and the pH value is adjusted to 8-13, the obtained Pd salt solution is added thereto, and H4N2·H2O is added for stirring reaction, so as to finally obtain a Pd hydride catalyst supported on a carbon carrier.

[0004] In all of the above processes, the catalytically active substances are directly loaded on the surface of the carbon carrier, and all of them have the disadvantages that the carbon carrier is prone to agglomeration, the carbon carrier has relatively few active sites, and the catalytically active substances are difficult to control.

[0005] Therefore, how to avoid the agglomeration of catalyst carriers and provide more active sites for substances with catalytic activity is an urgent problem to be solved. Summary of the invention

[0006] In view of the above problems existing in the prior art, the object of the present invention is to provide a catalyst carrier and a preparation method and application thereof.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a catalyst carrier, the catalyst carrier comprising a carbon carrier, a nitrogen-doped carbon coating layer and cerium oxide (CeO2), wherein the nitrogen-doped carbon coating layer is coated on the surface of the carbon carrier, and the CeO2 is dispersed in the nitrogen-doped carbon coating layer;

[0009] Wherein, the carbon carrier is carbon nanotube and / or fullerene.

[0010] In the present invention, the surface of the carbon carrier in the catalyst carrier is coated with a nitrogen-doped carbon coating layer, CeO2 is dispersed in the nitrogen-doped carbon coating layer, and CeO2 is dispersed in the nitrogen-doped carbon coating layer. 4+ The chemical durability of the proton exchange membrane can be improved by eliminating free radicals through redox reaction with ·OH free radicals; and the nitrogen-doped carbon coating provides more active sites for CeO2, so that CeO2 is evenly dispersed in the nitrogen-doped carbon coating. In addition, the nitrogen-doped carbon coating and CeO2 weaken the van der Waals force between carbon carriers, effectively improving the dispersibility of carbon carriers.

[0011] Preferably, the length of the catalyst carrier is 5-15 μm, for example 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.

[0012] Preferably, the outer diameter of the catalyst carrier is 40-60 nm, for example 40 nm, 45 nm, 50 nm, 55 nm or 60 nm.

[0013] The length and outer diameter of the catalyst carrier are preferably within the above ranges, so that it has a long-range and orderly proton transport channel constructed with a larger aspect ratio, which is beneficial to improving the proton conduction capacity of the catalyst carrier.

[0014] Preferably, the nitrogen-doped carbon coating layer is obtained by carbonizing a nitrogen-containing polymer having a benzene ring.

[0015] Illustratively, the nitrogen-containing polymer having a benzene ring includes, but is not limited to, polyaniline or polypyrrole.

[0016] Preferably, the particle size of CeO2 is 5-30nm, for example, 5nm, 8nm, 11nm, 14nm, 17nm, 20nm, 23nm, 26nm or 30nm.

[0017] In the present invention, due to the poor compatibility problem when inorganic oxides are doped with organic matter, if the particle size of CeO2 is too large, it is easy to cause membrane electrode defects, and if the particle size of CeO2 is too small, it is easy to be lost in a water-containing state.

[0018] Preferably, based on the total weight of the catalyst carrier as 100wt%, the total content of the carbon carrier and the nitrogen-doped carbon coating is 40-80wt%, for example, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%.

[0019] In the present invention, when the contents of the carbon carrier and the nitrogen-doped carbon coating layer are within the above range, on the one hand, the integrity of the carbon carrier coating can be ensured, and on the other hand, agglomeration of aniline during polymerization can be avoided.

[0020] Preferably, based on the total weight of the catalyst carrier as 100wt%, the content of CeO2 is 20-60wt%, for example 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt% or 60wt%.

[0021] If the CeO2 content is too high, it will easily lead to poor interface compatibility, causing product cracking and reducing the mechanical properties of the product. If the CeO2 content is too low, the free radical quenching effect of CeO2 will not be obvious.

[0022] In a second aspect, the present invention provides a method for preparing the catalyst carrier according to the first aspect, the method comprising the following steps:

[0023] (1) mixing a carbon support, a nitrogen-containing polymer monomer having a benzene ring, and a cerium salt initiator in a solvent to carry out a polymerization reaction;

[0024] (2) adding a precipitant to the solution after the polymerization reaction to carry out a reaction to obtain a first precursor;

[0025] (3) Heat treating the first precursor to obtain the catalyst carrier.

[0026] In the process of preparing the catalyst carrier of the present invention, the carbon carrier is used as the matrix, the nitrogen-containing polymer monomer with a benzene ring is polymerized under the initiation of the cerium salt initiator, and the formed polymer is coated on the carbon carrier, and Ce 4+ Dispersed in the formed polymer, and then under the action of the precipitant, Ce 4+ A precipitate is formed and dispersed in the polymer to prepare a first precursor, and the first precursor is heat-treated. After the heat treatment, a nitrogen-doped carbon coating is formed on the surface of the carbon carrier, and the nitrogen-doped carbon coating provides more active sites for CeO2, so that CeO2 is evenly dispersed in the nitrogen-doped carbon coating, avoiding partial precipitation of CeO2 outside the carbon carrier; in addition, the nitrogen-doped carbon coating and CeO2 weaken the van der Waals force between the carbon carrier, effectively improving the dispersibility of the carbon carrier.

[0027] The surface of the carbon carrier in the present invention has a five-membered ring or a six-membered ring, and the nitrogen-containing polymer with a benzene ring can undergo a conjugated reaction with the carbon carrier to improve the coating effect.

[0028] It should be noted that if the nitrogen-containing polymer with benzene rings is not coated on the surface of the carbon support, and the carbon support, cerium salt initiator and precipitant are directly reacted, CeO2 cannot be evenly dispersed on the surface of the carbon support, and CeO2 is easily deposited on other parts outside the carbon support, thereby affecting the performance of the prepared catalyst support.

[0029] The present invention does not limit the diameter of the carbon carrier. Exemplarily, the diameter of the carbon carrier in step (1) is 40-60 nm, such as 40 nm, 45 nm, 50 nm, 55 nm or 60 nm.

[0030] The present invention does not limit the length of the carbon carrier. Exemplarily, the length of the carbon carrier in step (1) is 5-15 μm, such as 5 μm, 8 μm, 11 μm, 14 μm or 15 μm.

[0031] Preferably, the nitrogen-containing polymer monomer having a benzene ring in step (1) comprises at least one of an aniline monomer or a pyrrole monomer.

[0032] Preferably, the cerium salt initiator in step (1) comprises ammonium cerium nitrate.

[0033] In the present invention, the cerium salt initiator serves as an initiator for the polymerization reaction in step (1) and provides Ce in the reaction system. 4+ .

[0034] Preferably, the cerium salt initiator in step (1) is added in the form of an aqueous solution of the cerium salt initiator.

[0035] Preferably, the concentration of the aqueous solution of the cerium salt initiator is 5-50 mg / mL, for example 5 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL or 50 mg / mL, preferably 10-30 mg / mL.

[0036] Preferably, the solvent in step (1) comprises a water-alcohol mixed solution.

[0037] Preferably, based on the total volume of the solvent as 100 vol%, the water content in the hydroalcoholic solution is 30-90 vol%, such as 30 vol%, 40 vol%, 50 vol%, 60 vol%, 70 vol%, 80 vol% or 90 vol%.

[0038] Preferably, the polymerization reaction in step (1) is carried out at a pH of 2-5 (eg, 2, 2.5, 3, 3.5, 4, 4.5 or 5, etc.).

[0039] Preferably, the polymerization reaction in step (1) is carried out under ice bath conditions.

[0040] In the present invention, the polymerization reaction is carried out under ice bath conditions, which means that the reaction container is placed in ice water. The purpose of carrying out the reaction under ice bath conditions is to prevent the polymerization rate of aniline from being too fast, and to reduce the polymerization rate of aniline by lowering the temperature, so as to achieve the requirement of uniform coating of polyaniline.

[0041] Preferably, the polymerization reaction in step (1) is carried out under a protective atmosphere.

[0042] Exemplarily, the gas in the protective atmosphere includes, but is not limited to, at least one of nitrogen, helium, argon or neon.

[0043] Preferably, the polymerization reaction time in step (1) is 10-30 h, for example 10 h, 15 h, 20 h, 22 h, 24 h, 26 h, 28 h or 30 h.

[0044] Preferably, the precipitant in step (2) comprises at least one of sodium hydroxide or potassium hydroxide.

[0045] Preferably, the precipitant in step (2) is added in the form of a precipitant solution, and the concentration of the precipitant solution is 10-100 mg / mL, for example, 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL or 100 mg / mL, preferably 30-80 mg / mL.

[0046] Preferably, the mass of the precipitant in step (2) is 0.5-1.5 times the mass of the cerium salt initiator.

[0047] Preferably, the reaction temperature in step (2) is 25-35°C, for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C.

[0048] Preferably, the reaction time in step (2) is 20-30 h, for example 20 h, 22 h, 24 h, 26 h, 28 h or 30 h.

[0049] Preferably, the first precursor is dried before the heat treatment in step (3).

[0050] Preferably, the drying temperature is 40-60°C, for example, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C.

[0051] Preferably, the heat treatment in step (3) is carried out under a protective atmosphere.

[0052] Exemplarily, the gas in the protective atmosphere includes, but is not limited to, at least one of nitrogen, helium, argon or neon.

[0053] Preferably, the temperature of the heat treatment in step (3) is 600-1600°C, for example 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C.

[0054] Preferably, the heat treatment time in step (3) is 2-10 h, for example 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.

[0055] In a third aspect, the present invention provides a catalyst, wherein the catalyst comprises the catalyst carrier as described in the first aspect of the present invention.

[0056] The catalyst in the present invention comprises the catalyst carrier described in the first aspect of the present invention, and the nitrogen-doped carbon coating layer and CeO2 in the catalyst carrier improve the catalytic reduction activity and mass activity of the catalyst.

[0057] Preferably, the catalyst also includes a catalyst active component.

[0058] Preferably, the catalyst active component comprises a noble metal.

[0059] The present invention does not limit the type of precious metal. By way of example, the precious metal includes but is not limited to platinum or platinum alloy.

[0060] Preferably, the mass ratio of the catalyst active component to the catalyst carrier described in the first aspect of the present invention is (0.3-0.7):1, and "0.3-0.7" can be, for example, 0.3, 0.4, 0.5, 0.6 or 0.7.

[0061] The present invention does not limit the preparation method of the catalyst. Exemplarily, the preparation method of the catalyst includes:

[0062] (1) The catalyst support described in the first aspect of the present invention and a reducing agent are mixed to form a suspension solution.

[0063] (2) Adding the catalyst active component to the suspension solution in step (1), stirring, and then subjecting the solution to microwave treatment in a microwave oven to prepare the catalyst.

[0064] Illustratively, the reducing agent includes but is not limited to ethylene glycol.

[0065] In a fourth aspect, the present invention provides a battery, wherein the battery comprises the catalyst described in the third aspect of the present invention.

[0066] The catalyst described in the third aspect of the present invention can increase the electrochemical active area (ECSA) and mass activity (MA) of the battery.

[0067] Preferably, the battery comprises a fuel cell or a metal-air battery.

[0068] The present invention does not limit the type of fuel cell. By way of example, the fuel cell includes but is not limited to at least one of a hydrogen fuel cell, a methanol fuel cell or a methane fuel cell.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] (1) The surface of the carbon carrier in the catalyst carrier of the present invention is coated with a nitrogen-doped carbon coating layer, and CeO2 is dispersed in the nitrogen-doped carbon coating layer. The nitrogen-doped carbon coating layer provides more active sites for CeO2, so that CeO2 is evenly dispersed in the nitrogen-doped carbon coating layer. In addition, the nitrogen-doped carbon coating layer and CeO2 weaken the van der Waals force between the carbon carriers, effectively improving the dispersibility of the carbon carriers.

[0071] (2) The preparation method of the catalyst carrier in the present invention retains the characteristics of the carbon carrier to a large extent. The prepared catalyst carrier has a long-range orderly proton transport channel constructed with a large aspect ratio, which is beneficial to improving the proton conduction capacity.

[0072] (3) The present invention introduces CeO2 in situ, and the OH radicals generated at the catalyst are preferentially 4+Oxidation prevents the proton exchange membrane in the hydrogen fuel cell from being attacked by free radicals OH, thereby extending the service life of the proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 It is a transmission electron microscope (TEM) image of the catalyst support in Comparative Example 2 of the present invention;

[0074] Figure 2 TEM image of the catalyst support in Example 1 of the present invention;

[0075] Figure 3 This is the X-ray diffraction (XRD) diagram of the catalyst carrier in Example 1 of the present invention. DETAILED DESCRIPTION

[0076] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0077] In the embodiments of the present invention, "normal temperature" refers to 25°C.

[0078] The carbon carrier used in the embodiment of the present invention is multi-walled carbon nanotubes (MWCNTs).

[0079] Example 1

[0080] This embodiment provides a catalyst carrier, which includes MWCNTs, a nitrogen-doped carbon coating layer and CeO2, wherein the nitrogen-doped carbon coating layer is coated on the surface of the MWCNTs, and the CeO2 is dispersed in the nitrogen-doped carbon coating layer.

[0081] Based on the total weight of the catalyst carrier being 100 wt%, the total content of the MWCNTs and the nitrogen-doped carbon coating layer is 60 wt%, the content of CeO2 is 40 wt%, and the particle size of CeO2 is 5 nm.

[0082] The preparation method of the catalyst carrier is as follows:

[0083] (1) Weigh 50 mg of MWCNTs (with a diameter in the range of 40-60 nm and a length in the range of 5-15 μm) and add them to 50 mL of a hydroalcoholic solution (30 mL of deionized water and 20 mL of ethanol). Use hydrochloric acid to adjust the pH value of the solution to 2. Then add 0.1 mol of aniline. After ultrasonic dispersion for 1 h, the obtained mixed solution is transferred to a magnetic stirring device for stirring. Prepare a 20 mg / mL Ce(NH4)2(NO3)6 aqueous solution, take 25 mL and slowly add it dropwise to the above mixed solution. React for 12 h under argon and ice bath conditions.

[0084] (2) After the reaction was completed, 10 mL of 60 mg / mL sodium hydroxide solution was added dropwise at room temperature and pressure, and the reaction was stirred for 24 h. The product was collected by vacuum filtration, and the obtained product was washed with water three times and then dried in a vacuum oven at 60°C.

[0085] (3) Grinding the dried product in step (2) into fine powder, and heat treating it in a tube furnace under the protection of nitrogen, the heat treatment temperature is 800° C., the heat treatment time is 4 h, and the catalyst carrier is prepared after the heat treatment.

[0086] Example 2

[0087] This embodiment provides a catalyst carrier, which includes MWCNTs, a nitrogen-doped carbon coating layer and CeO2, wherein the nitrogen-doped carbon coating layer is coated on the surface of the MWCNTs, and the CeO2 is dispersed in the nitrogen-doped carbon coating layer.

[0088] Based on the total weight of the catalyst carrier being 100 wt%, the total content of the MWCNTs and the nitrogen-doped carbon coating layer is 75 wt%, and the content of CeO2 is 25 wt%. The particle size of CeO2 is 10 nm.

[0089] The preparation method of the catalyst carrier is as follows:

[0090] (1) Weigh 50 mg of MWCNTs (with a diameter in the range of 40-60 nm and a length in the range of 5-15 μm) and add them to 50 mL of a hydroalcoholic solution (20 mL of deionized water and 30 mL of ethanol). Use hydrochloric acid to adjust the pH value of the solution to 4, then add 0.15 mol of aniline, and transfer the obtained mixed solution to a magnetic stirring device after ultrasonic dispersion for 1 h for stirring. Prepare a Ce(NH4)2(NO3)6 aqueous solution with a concentration of 10 mg / mL, take 60 mL and slowly add it dropwise to the mixed solution in step (1), and react for 16 h under argon and ice bath conditions.

[0091] (2) After the reaction was completed, 12 mL of 30 mg / mL sodium hydroxide solution was added dropwise at room temperature and pressure, and the reaction was stirred for 26 h. The product was collected by vacuum filtration, and the obtained product was washed with water three times and then dried in a vacuum oven at 40°C.

[0092] (3) Grinding the dried product in step (2) into fine powder, and heat treating it in a tube furnace under the protection of nitrogen, the heat treatment temperature is 1200° C., the heat treatment time is 6 hours, and the catalyst carrier is prepared after the heat treatment.

[0093] Example 3

[0094] This embodiment provides a catalyst carrier, which includes MWCNTs, a nitrogen-doped carbon coating layer and CeO2, wherein the nitrogen-doped carbon coating layer is coated on the surface of the MWCNTs, and the CeO2 is dispersed in the nitrogen-doped carbon coating layer.

[0095] Based on the total weight of the catalyst carrier being 100 wt%, the total content of the MWCNTs and the nitrogen-doped carbon coating layer is 55 wt%, and the content of CeO2 is 45 wt%. The particle size of CeO2 is 15 nm.

[0096] The preparation method of the catalyst carrier is as follows:

[0097] (1) Weigh 50 mg of MWCNTs (with a diameter in the range of 40-60 nm and a length in the range of 5-15 μm) and add them to 50 mL of a hydroalcoholic solution (40 mL of deionized water and 10 mL of ethanol). Use hydrochloric acid to adjust the pH value of the solution to 5, then add 0.1 mol of pyrrole, and transfer the obtained mixed solution to a magnetic stirring device after ultrasonic dispersion for 1 h for stirring. Prepare a Ce(NH4)2(NO3)6 aqueous solution with a concentration of 30 mg / mL, take 10 mL and slowly add it dropwise to the mixed solution in step (1), and react for 24 h under argon and ice bath conditions.

[0098] (2) After the reaction was completed, 5 mL of 80 mg / mL potassium hydroxide solution was added dropwise at room temperature and pressure, and the reaction was stirred for 20 h. The product was collected by vacuum filtration, and the obtained product was washed with water three times and then dried in a vacuum oven at 50°C.

[0099] (3) Grinding the dried product in step (2) into fine powder, and heat treating it in a tube furnace under the protection of argon at a temperature of 1400° C. for 2 h, to obtain the catalyst carrier after heat treatment.

[0100] Example 4

[0101] Compared with Example 1, the only difference is that, based on the total weight of the catalyst carrier being 100wt%, the total content of the MWCNTs and the nitrogen-doped carbon coating layer is 30wt%, and the content of CeO2 is 70wt%.

[0102] Example 5

[0103] Compared with Example 1, the only difference is that, based on the total weight of the catalyst carrier being 100wt%, the content of the MWCNTs and the nitrogen-doped carbon coating layer is 90wt%, and the content of CeO2 is 10wt%.

[0104] Comparative Example 1

[0105] Compared with Example 1, the only difference is that aniline is not added in step (1).

[0106] Comparative Example 2

[0107] Compared with Example 1, the only difference is that no precipitation agent sodium hydroxide solution is added in step (2).

[0108] Comparative Example 3

[0109] The only difference compared with Example 1 is that no heat treatment is performed.

[0110] Application Example 1

[0111] This application example provides a catalyst, wherein the catalyst carrier in the catalyst is the catalyst carrier in Example 1, the catalytically active component in the catalyst is platinum, and the mass ratio of the catalyst active component to the catalyst carrier in Example 1 is 0.5:1.

[0112] The preparation method of the catalyst is as follows:

[0113] (1) 100 mg of the catalyst support in Example 1 and 250 mL of ethylene glycol were mixed to form a suspension solution, and the suspension solution was mixed by ultrasonication, cell disruption and high-speed shearing, wherein the ultrasonication time was 30 min, the cell disruption time was 5 min, the high-speed shearing time was 10 min, and the high-speed shearing speed was 8000 rpm;

[0114] (2) Add 105 mg of chloroplatinic acid to the suspension solution in step (1), stir evenly, and microwave the obtained suspension solution in a microwave oven for 30 min to prepare the catalyst.

[0115] Application Example 2

[0116] Compared with Application Example 1, the only difference is that the catalyst carrier in Example 2 is used.

[0117] Application Example 3

[0118] Compared with Application Example 1, the only difference is that the catalyst carrier in Example 3 is used.

[0119] Application Example 4

[0120] Compared with Application Example 1, the only difference is that the catalyst carrier in Example 4 is used.

[0121] Application Example 5

[0122] Compared with Application Example 1, the only difference is that the catalyst carrier in Example 5 is used.

[0123] Application Example 1

[0124] Compared with Application Example 1, the only difference is that the catalyst carrier in Comparative Example 1 is used.

[0125] Application Example 2

[0126] Compared with Application Example 1, the only difference is that the catalyst carrier in Comparative Example 2 is used.

[0127] Application Example 3

[0128] Compared with Application Example 1, the only difference is that the catalyst carrier in Comparative Example 3 is used.

[0129] Figure 1 TEM image of the catalyst support in Comparative Example 2. Figure 1 It can be seen that a uniform nitrogen-doped carbon coating layer is formed on the surface of MWCNTs.

[0130] Figure 2 TEM image of the catalyst support in Example 1 of the present invention. Figure 2 It can be seen that a uniform nitrogen-doped carbon coating layer is formed on the surface of MWCNTs, and CeO2 is relatively evenly dispersed in the nitrogen-doped carbon coating layer. The thickness of the formed coating layer is in the range of 20-30 nm.

[0131] Figure 3 The XRD pattern of the catalyst support in Example 1 of the present invention, the test angle is 5-90°, Table 1 is the relationship between the XRD scanning angle (2θ) and the crystal plane index of pure CeO2 (JCPDS34-0394 PDF standard card), Figure 3 As can be seen from Table 1, the degree of characteristic peaks and crystal plane index of the XRD pattern of the catalyst support in Example 1 of the present invention correspond to Table 1, indicating that the catalyst support in Example 1 of the present invention has CeO2, and Figure 3 The XRD curve in FIG. 1 has no impurity peaks or noise except for the characteristic peak of carbon (C) at 26°, indicating that the purity of CeO2 in the catalyst carrier in Example 1 is relatively high.

[0132] Table 1

[0133] 2θ(°) 28.46 32.96 47.32 56.16 58.9 69.1 76.52 78.88 88.26 Crystalline index (111) (200) (220) (311) (222) (400) (331) (420) (422)

[0134] Performance testing:

[0135] The ECSA and MA of the catalyst in Example 1-5 and Application Comparative Example 1-3 were tested using 0.1 mol / L perchloric acid electrolyte. The test conditions of ECSA were to keep nitrogen gas flowing, not to open the speed, the potential interval was 0.025V-1.2V (vs. RHE), the scanning rate was 50mV / s, and the scanning was 3 circles; the MA test conditions were to pass oxygen through the electrolyte for 30min before the test, so that the electrolyte was in an oxygen-saturated state, and the electrode speed was adjusted to 1600rpm during the test, the potential interval was 0-1.2V (vs. RHE), the scanning rate was 10mV / s, and the forward scanning was performed. The results of the test are shown in Table 2.

[0136] Table 2

[0137] <![CDATA[ECSA(m 2 / g)]]> MA (mA / mg) Application Example 1 60 220 Application Example 2 57 210 Application Example 3 53 205 Application Example 4 40 168 Application Example 5 38 156 Comparative Application Example 1 20 130 Comparative Application Example 2 50 196 Comparative Application Example 3 10 90

[0138] analyze:

[0139] It can be seen from the data of Application Examples 1-5 that the catalyst prepared using the catalyst carrier in the embodiment of the present invention has higher ECSA and MA. This is mainly because the catalyst carrier in the embodiment of the present invention has a long-range ordered proton transport channel constructed with a larger aspect ratio, which is beneficial to improving the proton conduction capacity.

[0140] It can be seen from the data of Application Example 1 and Application Examples 4-5 that the total content of MWCNTs and nitrogen-doped carbon coating and the content of CeO2 in the catalyst carrier in the embodiment of the present invention have an important influence on the performance of the prepared catalyst carrier. Only when the total content of MWCNTs and nitrogen-doped carbon coating and the content of CeO2 are in a suitable ratio can the ECSA and MA of the prepared catalyst carrier be better improved.

[0141] It can be seen from the data of Application Example 1 and Application Control Examples 1-2 that only the nitrogen-doped carbon coating or only CeO2 cannot effectively improve the ECSA and MA of the prepared catalyst support. Only when the nitrogen-doped carbon coating and CeO2 are simultaneously coated on the surface of MWCNTs can the ECSA and MA of the catalyst support be effectively improved.

[0142] It can be seen from the data of Application Example 1 and Application Control Example 3 that whether or not heat treatment is performed has a great influence on the performance of the prepared catalyst carrier. When heat treatment is not performed, a nitrogen-doped carbon coating layer cannot be formed on the surface of MWCNTs, and CeO2 cannot be guaranteed to be evenly dispersed in the nitrogen-doped carbon coating layer.

[0143] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A catalyst, It is characterized in that The catalyst comprises a catalyst carrier and a catalyst active component; the catalyst active component comprises a noble metal; the mass ratio of the catalyst active component to the catalyst carrier is (0.3-0.7):1; The catalyst support comprises a carbon support, a nitrogen-doped carbon coating layer and CeO 2 The nitrogen-doped carbon coating layer is coated on the surface of the carbon carrier, and the CeO 2 dispersed in the nitrogen-doped carbon coating layer; Wherein, the carbon carrier is carbon nanotube and / or fullerene; Based on the total weight of the catalyst carrier being 100 wt%, the total content of the carbon carrier and the nitrogen-doped carbon coating layer is 40-80 wt%, and the CeO 2 The content is 20-60wt%; The thickness of the nitrogen-doped carbon coating layer is 20-30 nm.

2. The catalyst according to claim 1, It is characterized in that The length of the catalyst carrier is 5-15 μm.

3. The catalyst according to claim 1, It is characterized in that The outer diameter of the catalyst carrier is 40-60 nm.

4. The catalyst according to claim 1, It is characterized in that The nitrogen-doped carbon coating layer is obtained by carbonizing a nitrogen-containing polymer having a benzene ring.

5. The catalyst according to claim 1, It is characterized in that The CeO 2 The particle size is 5-30nm.

6. A method for preparing the catalyst according to any one of claims 1 to 5, It is characterized in that The method comprises the following steps: (1) mixing a carbon support, a nitrogen-containing polymer monomer having a benzene ring, and a cerium salt initiator in a solvent to carry out a polymerization reaction; (2) adding a precipitant to the solution after the polymerization reaction to carry out a reaction to obtain a first precursor; (3) thermally treating the first precursor to obtain the catalyst support; (4) mixing a catalyst carrier and a reducing agent to form a suspension, adding a catalyst active component to the suspension, stirring the suspension, and then subjecting the suspension to microwave treatment in a microwave oven to prepare the catalyst; The solvent in step (1) comprises a water-alcohol mixed solution; The temperature of the heat treatment in step (3) is 800-1600°C.

7. The method according to claim 6, It is characterized in that The nitrogen-containing polymer monomer having a benzene ring in step (1) comprises at least one of an aniline monomer or a pyrrole monomer.

8. The method according to claim 6, It is characterized in that The cerium salt initiator in step (1) includes ammonium cerium nitrate.

9. The method according to claim 6, It is characterized in that The cerium salt initiator in step (1) is added in the form of an aqueous solution of the cerium salt initiator.

10. The method according to claim 9, It is characterized in that The concentration of the aqueous solution of the cerium salt initiator is 5-50 mg / mL.

11. The method according to claim 10, It is characterized in that The concentration of the aqueous solution of the cerium salt initiator is 10-30 mg / mL.

12. The method according to claim 6, It is characterized in that Based on the total volume of the solvent being 100 vol%, the water content in the water-alcohol mixed solution is 30-90 vol%.

13. The method according to claim 6, It is characterized in that The polymerization reaction in step (1) is carried out at a pH of 2-5.

14. The method according to claim 6, It is characterized in that The polymerization reaction in step (1) is carried out under ice bath conditions.

15. The method according to claim 6, It is characterized in that The polymerization reaction in step (1) is carried out under a protective atmosphere.

16. The method according to claim 6, It is characterized in that The polymerization reaction time in step (1) is 10-30 hours.

17. The method according to claim 6, It is characterized in that The precipitant in step (2) includes at least one of sodium hydroxide or potassium hydroxide.

18. The method according to claim 6, It is characterized in that The precipitant in step (2) is added in the form of a precipitant solution, and the concentration of the precipitant solution is 10-100 mg / mL.

19. The method according to claim 18, It is characterized in that The concentration of the precipitant solution is 30-80 mg / mL.

20. The method according to claim 6, It is characterized in that The mass of the precipitant in step (2) is 0.5-1.5 times the mass of the cerium salt initiator.

21. The method according to claim 6, It is characterized in that The reaction temperature in step (2) is 25-35°C.

22. The method according to claim 6, It is characterized in that The reaction time of step (2) is 20-30 hours.

23. The method according to claim 6, It is characterized in that The first precursor is dried before the heat treatment in step (3).

24. The method according to claim 23, It is characterized in that The temperature of the drying process is 40-60°C.

25. The method according to claim 6, It is characterized in that The heat treatment in step (3) is carried out under a protective atmosphere.

26. The method according to claim 6, It is characterized in that The heat treatment time in step (3) is 2-10 hours.

27. A battery, It is characterized in that The battery comprises the catalyst according to any one of claims 1 to 5.

28. The battery according to claim 27, It is characterized in that The battery includes a fuel cell or a metal-air battery.

Citation Information

Patent Citations

  • Preparation method of Ni-based catalyst modified by aid Pt supported by multi-wall carbon nanotube as carrier and application

    CN107649148A

  • Platinum-boron co-doped supported palladium-based catalyst as well as preparation method and application thereof

    CN114990579A

  • Pd hydride catalyst for direct alcohol fuel cell and preparation method of Pd hydride catalyst

    CN115000424A

  • Carbon supported non-noble metal oxygen reduction compound catalyst, and preparation method and application thereof

    CN103515624A

  • Oxygen reduction catalyst as well as preparation method and application of oxygen reduction catalyst

    CN103949251A